Infrared and Raman Spectra, Ab Initio Calculations Vibrational Assignment of 4-Aminosalicylic Acid - Akkaya, Yasemin; AKYÜZ, SEVİM (Elsevier, 2006)
The experimental and theoretical study on the structures and vibrations of 4-aminosalicylic acid are presented. The infrared spectra (4000–400 cm−1) and the Raman spectra (4000–50 cm−1) of the molecule in solid phase have been measured. There are seven stable conformers, C1,C2, C3, C4, C5, C6, and C7 for this molecule. The computational results identify the most stable conformer of 4-aminosalicylic acid as the C1 form. The geometrical parameters and energies have been obtained for all seven conformers from ab-initio calculations. The vibrations of the five more stable conformers of 4-aminosalicylic acid are investigated with the aid of quantum chemical calculations. The spectroscopic and theoretical results are compared to the corresponding properties for 4-aminosalicylic dimer of C1 conformers.
Keywords: Ab Initio Calculations; 4-Aminosalicylic Acid; Infrared Spectra; Raman Spectra